Discovery of Ibomycin, a Complex Macrolactone that Exerts Antifungal Activity by Impeding Endocytic Trafficking and Membrane Function. Issue 11 (17th November 2016) - Robbins, Nicole; Spitzer, Michaela; Wang, Wenliang; Waglechner, Nicholas; Patel, Dhruv J.; O'Brien, Jonathan S.; Ejim, Linda; Ejim, Obi; Tyers, Mike; Wright, Gerard D.
Summary: Natural products are invaluable historic sources of drugs for infectious diseases; however, the discovery of novel antimicrobial chemical scaffolds has waned in recent years. Concurrently, there is a pressing need for improved therapeutics to treat fungal infections. We employed a co-culture screen to identify ibomycin, a large polyketide macrolactone that has preferential killing activity against Cryptococcus neoformans . Using chemical and genome methods, we determined the structure of ibomycin and identified the biosynthetic cluster responsible for its synthesis. Chemogenomic profiling coupled with cell biological assays link ibomycin bioactivity to membrane function. The preferential activity of ibomycin toward C. neoformans is due to the ability of the compound to selectively permeate its cell wall. These results delineate a novel antifungal agent that is produced by one of the largest documented biosynthetic clusters to date and underscore the fact that there remains significant untapped chemical diversity of natural products with application in antimicrobial research. Graphical Abstract: Highlights: Use of a co-culture screen discovers a novel large polyketide termed ibomycin Ibomycin has preferential activity against the fungal pathogen C. neoformans Three biosynthetic clusters are responsible for the synthesis of ibomycin Chemogenomic profiling links ibomycin bioactivity to membrane function Abstract : A co-culturing screen identified a molecule termed ibomycin with preferential activity against Cryptococcus neoformans. The specific action was due to the ability of ibomycin to cross the cell wall to affect membrane function. Thus, natural products remain a rich source of antimicrobials.